Prevalence and antimicrobial susceptibility patterns of Shigella in stool samples in a tertiary healthcare hospital of Punjab - Atul Kumar; Aroma Oberoi; Vipin Sam Alexander (Wolters Kluwer Medknow Publications, 2014)
Background: Shigella is an important cause of invasive dysentery in children and others. The present study was done to study the prevalence, any seasonal variation, distribution among children and adults, and antimicrobial susceptibility pattern of Shigella isolates in stool. Materials and Methods: A retrospective study was conducted over a period of 1 year from June 2011 to June 2012 in the department of microbiology, in a tertiary care hospital in Punjab. Stool specimens from diarrhea/dysentery cases in different age-groups were processed. The specimens were processed by standard microbiological techniques. The suspected colonies of Shigella were identified by standard biochemical tests and serotyping was done by group specific antisera. The susceptibility of all the isolated Shigella species to different antibiotics were done by Kirby-Bauer's disk diffusion technique as per the Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Shigella species were isolated from 30 (2.1%) of the total 1,402 stool samples received during the study period. Among these, Shigella flexneri was the predominant species accounting for 57% of isolates, followed by S. sonnei (36%) and S. boydii (7%). Over 70% of Shigella isolates were resistant to two or more drugs including ampicillin, trimethoprim-sulfamethoxazole, and norfloxacin; and 10% Shigella isolates were resistant to chloramphenicol and ceftriaxone during the study period. No resistance was observed to cefoperazone/sulbactam, piperacillin/tazobactam, and imipenem. Conclusions: The results of the study revealed the high prevalence of shigellosis with S. flexneri as the predominant species. The result also suggests that ampicillin, trimethoprim-sulfamethoxazole and norfloxacin should not be used empirically as the first line drugs in the treatment of shigellosis. Periodic analysis and reporting of antibiotic susceptibility is an important measure to check for antibiotic resistance and form appropriate treatment protocols.